Reported cases of domestic violence, sexual violence and/or other violence in elderly in the municipality of santa maria- rs - Santos, Tamires Daros dos (2018)
Objective: to characterize reported cases of domestic violence, sexual violence and / or other violence in the elderly in the municipality of Santa Maria-RS in the period 2010-2014. Method: a secondary, descriptive, retrospective study, carried out with data from the Department of Informatics of the Unified Health System (DATASUS) through the Health Information made available in Tabnet. Results: There was an increase in the number of cases of violence against the elderly reported in the municipality of Santa Maria-RS in the period analyzed, totaling 95 cases. Considering the profile, male predominance (53.7%), white race (80%) and incomplete elementary school (58.9%) were observed. There was a predominance of physical violence (41%) followed by neglect / abandonment (21%). Repeat violence was reported in 21% of cases. The most frequent means of aggression was body violence / beatings, place of occurrence at residence (70.5%) and likely offender (60%). Conclusion: The number of cases of reports of violence against the elderly has increased over the years (2010-2014) in the municipality of Santa Maria-RS. The profile of the elderly can be characterized as man, white and with low level of schooling, victims of physical violence, practiced by means of corporal violence / beating, in the residence, having as probable aggressor the son and as end result of hospital discharge.